2018
DOI: 10.1038/s41396-018-0290-y
|View full text |Cite
|
Sign up to set email alerts
|

From proteins to polysaccharides: lifestyle and genetic evolution of Coprothermobacter proteolyticus

Abstract: Microbial communities that degrade lignocellulosic biomass are typified by high levels of species- and strain-level complexity, as well as synergistic interactions between both cellulolytic and non-cellulolytic microorganisms. Coprothermobacter proteolyticus frequently dominates thermophilic, lignocellulose-degrading communities with wide geographical distribution, which is in contrast to reports that it ferments proteinaceous substrates and is incapable of polysaccharide hydrolysis. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…Furthermore, it was surprising and notable that the consortium was predominantly composed of Methanothermobacter and Coprothermobacter, which were both highly abundant at 59, 62, and 65 °C (Figure 3a and b), and some researchers have reported that Coprothermobacter can also perform syntrophic acetic oxidation (SAO). 1,30 This result is slightly inconsistent with the cluster based on cumulative CH 4 production (Figure S1). Additionally, the intracluster similarity at 59−65 °C was significantly higher in the cluster dendrogram than in other clusters, which indicates that the microbial community structural changes at 59−65 °C are less dynamic than those at other temperatures.…”
Section: ■ Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Furthermore, it was surprising and notable that the consortium was predominantly composed of Methanothermobacter and Coprothermobacter, which were both highly abundant at 59, 62, and 65 °C (Figure 3a and b), and some researchers have reported that Coprothermobacter can also perform syntrophic acetic oxidation (SAO). 1,30 This result is slightly inconsistent with the cluster based on cumulative CH 4 production (Figure S1). Additionally, the intracluster similarity at 59−65 °C was significantly higher in the cluster dendrogram than in other clusters, which indicates that the microbial community structural changes at 59−65 °C are less dynamic than those at other temperatures.…”
Section: ■ Resultsmentioning
confidence: 70%
“…Very surprisingly, a high proportion of Coprothermobacter appeared in an AD system using glucose as the substrate. According to a previous study by Kunath et al, Coprothermobacter not only ferment proteinaceous substrates but also promote the degradation of polysaccharides. In addition, Han et al reported that Coprothermobacter act as scavengers and/or predators and perform proteolysis and fermentation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetate-oxidizing bacteria (mainly Thermacetogenium) converted acetate into H 2 and CO 2 , both from the feed organics and from hydrolysis, which was then utilized syntrophically by the hydrogenotrophic methanogens (mainly Methanothermobacter) to produce methane (Figure 7). Notably, the predominant genus in the thermophilic anaerobic digester was reported to be Coprothermobacter (Gagliano et al, 2015), which may also function as SAO (Lu et al, 2014;Kunath et al, 2019). The high α c and f mh values supported the role of HM pathway in methane production.…”
Section: Microbial Community Structure Reconstruction and Methanogenementioning
confidence: 94%